From compound culture to benchmark culture : the transformation and development of BNBM - Liao, Hui, 1975-; Zheng, Xiaoming; Cao, Shanshan (London : Tsinghua University School of Economics and Management, 2017)
BNBM is a state owned Chinese enterprise that manufactures gypsum boards for the construction industry. The case examines the creation of ‘home culture' where BNBM cultivated a culture where the employees viewed the organization as their home.
Originally Published InLui, H., Zheng, X., & Cao, S. (2017). From Compound Culture to Benchmark Culture: The Transformation and Development of BNBM. 6-817-351. Beijing, China: Tsinghua SEM Chinese Business Case Center.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Bei xin jian cai (ji tuan) you xian gong si (China) -- Case studies; Corporate culture -- China -- Case studies; Drywall